Efek Kompetensi, Peran Perangkat Desa Dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa - Mispa, Sitti; Nuramal, Nuramal; Lalo, Annas; Hamzah, Izhak (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This research aims to determine and analyze the influence of competence, the role of village officials and the internal control system on the accountability of village fund management in Gantarang District, Bulukumba Regency. This research uses a quantitative approach, a method used to describe the condition of the company which is carried out using analysis based on quantitative data. This research was conducted at the village government in Benteng Gantarang Village and Dampang Village, Gantarang District, Bulukumba Regency. The population in this study was all village government officials in Benteng Gantarang Village and Dampang Village, Gantarang District, Bulukumba Regency, totaling 40 Village Officials. The sampling method is saturated sampling, the saturated sampling technique is a sample determination technique when all members of the population are used as samples. The data source in this research is primary data using questionnaire data collection techniques. The results of this research show that Competency (X1) has a positive and significant effect on the Accountability of Village Fund Management in Gantarang District, Bulukumba Regency (Y), the Role of Village Officials (X2) has a positive and significant effect on Accountability of Village Fund Management in Gantarang District, Bulukumba Regency ( Y), as well as the Internal Control System (X3) have no and no significant effect on the Accountability of Village Fund Management in Gantarang District, Bulukumba Regency (Y).